Evolution of metabolic capabilities and molecular features of diplonemids, kinetoplastids, and euglenids - Anzhelika Butenko; Fred R. Opperdoes; Olga Flegontova; Aleš Horák; Vladimír Hampl; Patrick Keeling; Ryan M. R. Gawryluk; Denis Tikhonenkov; Pavel Flegontov; Julius Lukeš (BMC Biology, 2020)
Abstract Background The Euglenozoa are a protist group with an especially rich history of evolutionary diversity. They include diplonemids, representing arguably the most species-rich clade of marine planktonic eukaryotes; trypanosomatids, which are notorious parasites of medical and veterinary importance; and free-living euglenids. These different lifestyles, and particularly the transition from free-living to parasitic, likely require different metabolic capabilities. We carried out a comparative genomic analysis across euglenozoan diversity to see how changing repertoires of enzymes and structural features correspond to major changes in lifestyles. Results We find a gradual loss of genes encoding enzymes in the evolution of kinetoplastids, rather than a sudden decrease in metabolic capabilities corresponding to the origin of parasitism, while diplonemids and euglenids maintain more metabolic versatility. Distinctive characteristics of molecular machines such as kinetochores and the pre-replication complex that were previously considered specific to parasitic kinetoplastids were also identified in their free-living relatives. Therefore, we argue that they represent an ancestral rather than a derived state, as thought until the present. We also found evidence of ancient redundancy in systems such as NADPH-dependent thiol-redox. Only the genus Euglena possesses the combination of trypanothione-, glutathione-, and thioredoxin-based systems supposedly present in the euglenozoan common ancestor, while other representatives of the phylum have lost one or two of these systems. Lastly, we identified convergent losses of specific metabolic capabilities between free-living kinetoplastids and ciliates. Although this observation requires further examination, it suggests that certain eukaryotic lineages are predisposed to such convergent losses of key enzymes or whole pathways. Conclusions The loss of metabolic capabilities might not be associated with the switch to parasitic lifestyle in kinetoplastids, and the presence of a highly divergent (or unconventional) kinetochore machinery might not be restricted to this protist group. The data derived from the transcriptomes of free-living early branching prokinetoplastids suggests that the pre-replication complex of Trypanosomatidae is a highly divergent version of the conventional machinery. Our findings shed light on trends in the evolution of metabolism in protists in general and open multiple avenues for future research.